POSSIBILITIES FOR INTEGRATING THE TEACHING OF NATURE AND SOCIETY AND ENGLISH LANGUAGE TEACHING THROUGH CONTENT ON NATURAL PHENOMENA - Petrić, Jelena (Metodička teorija i praksa, 2024)
Integration in teaching refers to the connection of content from different subjects, allowing students to acquire comprehensive knowledge and better understand the world around them. The importance of this approach lies in fostering critical thinking and applying learned concepts in real-life situations. The aim of this research was to determine the existence of similar or identical educational content on natural phenomena in the curricula for the subjects World Around Us/Nature and Society and English language, and explore possibilities for their integration. To conduct the research, we used the descriptive method, with content analysis as the main technique. The content analysis corpus consisted of curricula for the first four grades of primary school, specifically their segments related to the aforementioned subjects. Our analysis revealed that these subjects contain similar or identical content on natural phenomena, which could serve as a basis for integration. However, they are not fully aligned, as there are topics covered in one subject but not in the other within individual grades. Additionally, there are some natural phenomena topics that are covered in different grades across these two subjects.
Keywords: integrative teaching; World Around Us/Nature and Society; English language teaching; Natural phenomena